Knee Recurvatum in Children With Spastic Diplegic Cerebral Palsy. Issue 9 (October 2019) - Bauer, Jeremy; Patrick Do, K.; Feng, Jing; Pierce, Rosemary; Aiona, Michael
Abstract : Background: The purpose of this study is to determine which factors drive patients with diplegic cerebral palsy to walk without knee recurvatum despite hyperextension of the knee on physical examination. Methods: A retrospective review was conducted of all data collected in the Gait Analysis Laboratory between 1999 and 2014. Patients with spastic diplegic cerebral palsy and at least 5 degrees of knee extension on clinical examination were identified for the study. After IRB approval, a total of 60 children ranging in age from 4 to 17 were included in the study. There were 27 female patients. Gross Motor Function Classification System level was distributed in the population as follows: 34 patients at Gross Motor Function Classification System level I, 18 at level II, and 8 at level III. Patients were excluded from this study if they had extrapyramidal involvement, history of selective dorsal rhizotomy or lower extremity surgery. Patient who received botulinum toxin A injections within 1 year of the study were excluded as well. Patients were divided into 2 groups: children that walked with knee hyperextension (KH) and children that walked without knee hyperextension (KF, "knee flexion"). There were 15 subjects in the KH group and 45 subjects in the KF group. Motion Laboratory evaluation included a comprehensive examination, kinematics, and kinetic analysis with a VICOM system. All data were analyzed with unpaired t test to detect differences between the 2 groups. All statistical analysis was done only for the right legs (unless the right leg did not meet the exclusion then the left leg was analyzed) to meet the statistical requirement for independence. The Pearson correlation was applied to correlate the maximum knee extension in stance with maximum ankle dorsiflexion in stance. Results: The static measurement of dorsiflexion with knee flexed showed statistically significant difference ( P= 0.004) with KH group having 2.3±11.6 degrees and KF group having 13.1±12.2 degrees. There was also a statistically significant difference in the static measurement of dorsiflexion with knee extended ( P= 0.0014) with KH group having −3.3±9.0 degrees and KF group having 5.8±9.1 degrees. Maximum dorsiflexion in stance phase also showed significant difference ( P= 0.0022) with the KH group having 0.1±14.0 degrees and KF group having 11.5±11.2 degrees. Maximum dorsiflexion in stance phase also showed significant difference ( P <0.001) with the DH group having 0.1 (SD) 14.0 degrees and KF group having 11.5 (SD) 11.2 degrees. There were no significant differences in popliteal angle measurements or any strength measurement. Conclusions: Our study shows that the plantar flexion knee extension couple is the major contributing factor to cause patients with passive knee hyperextension to walk in a recurvatum pattern. This would have implications of further treatment of the knee hyperextension in stance. Level of Evidence: Level III—case-control study.